POTENSI MINYAK ATSIRI DAUN ANDALIMAN (Zanthoxylum acanthopodium) SEBAGAI ANTIVIRUS CORONA BERDASARKAN PENAMBATAN MOLEKUL - Endang Kintamani; Irmanida Batubara; Cecep Kusmana; Tatang Tiryana; Edi Mirmanto; Fikry Awaludin (BERITA BIOLOGI, 2022)
Andaliman (Zanthoxylum acanthopodium) plant, a unique spice in the Batak tribe limited only to the fruit. The leaves available most of the time and consisting of essential oils, there are no research has been conducted on molecular docking to determine the potential of the drug. The Covid-19 pandemic is still ongoing, so information as Corona antivirus is needed. This study aims to find the differences of chemical components from Andaliman leaves essential oil, classify the varieties, and get potential components as Corona antivirals based on molecular docking. The Andaliman leaves were collected from North Tapanuli District, than isolated using water distillation and Gas chromatography-mass spectrometry (GC-MS). Data analysis using Principal Component Analysis (PCA) with the XL stat 2020. The results showed that three varieties of Andaliman, Siholpu, Siganjangpat, and Variety three are not grouped in one quadrant. There are 53 compounds were detected. The dominant chemical compounds in all varieties are D-Limonene (Siganjangpat: 87.7%, Siholpu: 50.4%, and Variety three: 42.6%). Each variety is characterized by specific compounds, Siholpu by caryophyllene and sabinene; Singanjangpat by D-Limonene; Variety three by neryl acetate and 1,8-cinneol. The chemical component in Andaliman leaves that most potent as Corona antiviral is beta-caryophyllene in the Siholpu variety.